Efeito da embalagem e do tempo de armazenamento sobre a perda de vitamina c em pimentão (Capsicum annuum L.) desidratado - Stringheta, Paulo César; Teixeira Coelho, Dilson; Salustiano Pereira, Alonso; Paes Chaves, José Benício (Revista Ceres, 2025)
The paprika from different varieties of red pepper (Capsicum annuum L.) was used in the study of vitamin C retention during room temperature storage as affected by different storage times and packaging materials. The red pepper samples were first tunnel dried at 65°C for 10 hours before being ground into powder (paprika) and stored in a dessicator. Vitamin C assay was according to the method of Strohecker and Henning.